2016
DOI: 10.3855/jidc.7436
|View full text |Cite
|
Sign up to set email alerts
|

Reducing bacterial contamination in an Orthopedic Theatre ventilated by natural ventilation, in a Developing Country

Abstract: Introduction: All surgical procedures have the potential for infection and some of the main sources are contamination from airborne particles, theatre personnel and the theatre environment. There is strong evidence that the use of ultra-clean air flow systems in orthopedic operating theatres reduces the incidence of deep sepsis after surgery. In the developing world however, this is often an unrealistic solution. The aim of this study was to establish baseline levels of contamination in a working orthopedic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The cause of these surgical SSIs may be exogenous and several studies show that microorganisms can originate from the operation room (OR) environment 11-12-13-14 however, Gabriel Birgand et al reported that the impact of operating-room behaviours on the risk of infection were limited and heterogeneous. 15 This study has several limitations. Baselines characteristics as diabetes mellitus, smoking and Body Mass Index are not taken in account in this study.…”
Section: Study Populationmentioning
confidence: 92%
“…The cause of these surgical SSIs may be exogenous and several studies show that microorganisms can originate from the operation room (OR) environment 11-12-13-14 however, Gabriel Birgand et al reported that the impact of operating-room behaviours on the risk of infection were limited and heterogeneous. 15 This study has several limitations. Baselines characteristics as diabetes mellitus, smoking and Body Mass Index are not taken in account in this study.…”
Section: Study Populationmentioning
confidence: 92%
“…E.coli was described to be prevalent in operating beds due to fecal contamination and the lack of efficiency in the cleaning process [88,89]. Pseudomonas spp., one of the most significant genera of nosocomial pathogens, was the most prevalent bacteria in all operating theatres in the Matinyi et al study [38], and was identified in other studies [73,90] that referred to antiseptic solutions as a possible source of this contamination [56,57,91,92]. Other bacteria, Bacillus spp., can be related to dusty environments, the type commonly found in Uganda [38].…”
Section: Discussionmentioning
confidence: 90%
“…Trauma-related osteoarticular infections among patients with punctures wounds seeking medical care varied from 2-60% depending on the type of the injury [70][71][72]. S. aureus was also prevalent in the studies by Matinyi et al [38] and Thomas et al [73], being detected on door handles, which could be considered a possible source of nosocomial infection [38]. Additionally, Staphylococcus epidermidis, as well as Micrococcus luteus and Bacillus subtilis, were common in the studies by Sivagnanasundaram et al [50], Bielawska-Drózd et al [74], and Bolookat et al [39].…”
Section: Discussionmentioning
confidence: 99%
“…Those apparently conflicting findings imply that further research is required to identify optimal temperatures for the operating theaters. Maintaining such an optimal temperature also poses a special challenge for developing countries, where climate control in hospitals is often not feasible 4 …”
mentioning
confidence: 99%
“…To the Editor— Healthcare-associated infections (HAIs), and surgical site infections (SSIs) in particular, are more frequent in developing countries compared to Europe and the United States 1 2 Poor staff adherence to infection control guidelines in the operating theater has been blamed, 3 but environmental factors may also be involved in high SSI rates 4 …”
mentioning
confidence: 99%